2017
DOI: 10.1055/s-0036-1597286
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Pathophysiology of Antiphospholipid Syndrome

Abstract: The antiphospholipid syndrome (APS) is an autoimmune disorder characterized by an elevated risk for arterial and venous thrombosis and pregnancy-related morbidity. Since the discovery of the disease in 1980s, numerous studies in cell culture systems, in animal models, and in patient populations have been reported, leading to a deeper understanding of the pathogenesis of APS. These studies have determined that circulating autoantibodies, collectively called antiphospholipid antibodies (aPL), the majority of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 103 publications
1
19
0
3
Order By: Relevance
“…Вони включають сітчасте ліведо, тромбоцитопенію, Кумбс-позитивну гемолітичну анемію, антифосфоліпідну нефропатію, неврологічні прояви (хорея, поперечний мієліт, мігрені і когнітивна дисфункція, не обумовлена цереброваскулярними захворюваннями) і серцево-судинні прояви (частіше -ураження клапанів). Ці клінічні особливості пов'язані з циркулюванням аФЛ-АТ, які не завжди маніфестують тромбозами і акушерською патологією, а можуть бути пояснені такими механізмами, як запалення, активація комплементу і тромбоцитів [4,5].…”
Section: судинний тромбозunclassified
“…Вони включають сітчасте ліведо, тромбоцитопенію, Кумбс-позитивну гемолітичну анемію, антифосфоліпідну нефропатію, неврологічні прояви (хорея, поперечний мієліт, мігрені і когнітивна дисфункція, не обумовлена цереброваскулярними захворюваннями) і серцево-судинні прояви (частіше -ураження клапанів). Ці клінічні особливості пов'язані з циркулюванням аФЛ-АТ, які не завжди маніфестують тромбозами і акушерською патологією, а можуть бути пояснені такими механізмами, як запалення, активація комплементу і тромбоцитів [4,5].…”
Section: судинний тромбозunclassified
“…The exact mechanisms involved in the prothrombotic state of the disease (causing thrombosis and/or obstetric complications) remain yet to be fully explained. aPL have the ability to induce thrombus formation in the arterial and/ or venous vasculature and/or microcirculation by targeting and affecting the functionality of a variety of cell types such as endothelial cells, monocytes, leukocytes, neutrophils, and platelets on the vascular aspect of the disease, and trophoblasts and decidual cells during gestation; the irregular function of these cells contributes in the disease development [9]. Several studies have reported that aPLs have the capacity to interact with the trophoblast and the endothelial cell monolayer, by disrupting the anticoagulant annexin A5 shield, resulting in fetal loss [10].…”
Section: Pathogenesismentioning
confidence: 99%
“…Sacharidou et al therefore summarize the currently available data on the pathophysiology of APS. 17 Evidence from in vitro studies and animal models support the notion that vascular cells are activated by the circulating aPL. Furthermore, Muller-Calleja and Lackner provide an overview of the current insights in the way target cells are activated by aPL and discuss the data that support the role for the various cellular receptors that have been implicated in the pathophysiology of the syndrome.…”
mentioning
confidence: 95%